Acoustic characteristics of the Latvian sonorants - Grigorjevs, Juris (Baltistica, 2012)
The present article describes the spectral characteristics of the Latvian sonorants /m/, /n/ ([n] and [ŋ]), /ɲ/, /l/, /ʎ/ and /r/ as investigated in a pilot-study. The initial sonorant of the symmetric CVC syllables, as well as the formant transitions (CV) underwent spectral analysis. The obtained data suggest that the Latvian laterals are distinguished from the other sounds of Latvian and among themselves mainly on the basis of their formant structure. The principal cues for the Latvian nasals are provided by formant (mainly F2) transitions and the characteristic nasal murmur. It seems that the Latvian trill /r/ is characterized mainly by very brief partial or complete closures (weakening or omission of spectral energy) during the moments when the tongue tip touches the alveolar ridge. The formant structure of /r/ in the open phase is similar to that of the central vowels and depends on the quality of the following monophthong.